Optimisation of a TALE nuclease targeting the HIV co-receptor CCR5 for clinical application - Schwarze, Lea Isabell; Głów, Dawid; Sonntag, Tanja; Uhde, Almut; Fehse, Boris (Gene therapy, 2021)
Disruption of the C-C-Chemokine-receptor-5 ( CCR5 ) gene induces resistance towards CCR5-tropic HIV. Here we optimised our previously described CCR5-Uco-TALEN and its delivery by mRNA electroporation. The novel variant, CCR5-Uco-hetTALEN features an obligatory heterodimeric Fok1-cleavage domain, which resulted in complete abrogation of off-target activity at previously found homodimeric as well as 7/8 in silico predicted, potential heterodimeric off-target sites, the only exception being highly homologous CCR2 . Prevailing 18- and 10-bp deletions at the on-target site revealed microhomology-mediated end-joining as a major repair pathway. Notably, the CCR5 Δ55–60 protein resulting from the 18-bp deletion was almost completely retained in the cytosol. Simultaneous cutting at CCR5 and CCR2 induced rearrangements, mainly 15-kb deletions between the cut sites, in up to 2% of T cells underlining the necessity to restrict TALEN expression. We optimised in vitro mRNA production and showed that CCR5 -on- and CCR2 off-target activities of CCR5-Uco-hetTALEN were limited to the first 72 and 24–48 h post-mRNA electroporation, respectively. Using single-cell HRMCA, we discovered high rates of TALEN-induced biallelic gene editing of CCR5 , which translated in large numbers of CCR5-negative cells resistant to HIVenv-pseudotyped lentiviral vectors. We conclude that CCR5-Uco-hetTALEN transfected by mRNA electroporation facilitates specific, high-efficiency CCR5 gene-editing (30%–56%) and it is highly suited for clinical translation subject to further characterisation of off-target effects.